Mâles à Bars. (Paris : HPP, 2001)
Fonds Suzan Daniel (FSD)
Periodiciteit : wekelijksRedactie : 43/45 rue de la Roquette, 75011 Paris ; vanaf (2004) [1] : 121 rue de l'Ouest, 75014 Paris
Frans
Periodiek